A New Extended PR Conjugate Gradient Method for Solving Smooth Minimization Problems - Abbas Y. AL-Bayati; Rana Z. AL-Kawaz (المجلة العراقية للعلوم الاحصائية, 2011)
In this paper, we have discussed and investigated an extended PR-CG method which uses function and gradient values. The new method involves the extended CG-methods and have the sufficient descent and globally convergence properties under certain conditions. We have got some important numerical results by improving a standard computer program compared with Wu and Chen (2010) method in this field.